Using the legacy of Eastern thinkers in teaching arithmetic operations in elementary grades" (Eurasian Journal of Learning and Academic Teaching, 2023)
In this article, ideas were discussed about using the legacy of Eastern thinkers in teaching arithmetic operations in primary classes, correct application of arithmetic operations in examples, solving quick and easy problems with the help of today's modern technical tools.